2019
DOI: 10.1096/fasebj.2019.33.1_supplement.554.4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile and cytokine analysis in experimental autoimmune encephalomyelitis (EAE) in AVP deficient rats

Abstract: IntroductionHuman Multiple Sclerosis (MS) is a medically important disease. MS and its experimental autoimmune encephalomyelitis (EAE) paradigm are central nervous system demyelinizing diseases in which the immune system is directly involved. The pursuit for new treatments for MS still as an important goal for research. The use of the EAE animals to study the immune mechanisms that mediate the disease still being the best strategy to deep into the immune‐neuroendocrine interactions during the pathogenesis. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is evaluated by the effects of desmopressin, which increases the permeability of the BBB membrane. Evidence that AVP deficiency is responsible for the decreased immune response in the EAE rats is strongly supported by the similar decreased severity in the clinical symptoms and brain and spinal cord histopathological lymphocyte infiltrations with conivaptan, a specific V1a-V2 AVP receptors antagonist ( Quintanar-Stephano et al, 2012 ; Quintanar-Stephano et al, 2019 , 2018 ; Viñuela-Berni et al, 2020 ; Figure 2 ). On the other hand, Bossinger suggested that the administration of OXT in patients with MS during aggravation or remission periods alleviates the symptoms ( Bossinger, 1966 ); however, AVP and OXT can bind to V1a and V2 receptors ( Terrillon et al, 2003 ).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…This is evaluated by the effects of desmopressin, which increases the permeability of the BBB membrane. Evidence that AVP deficiency is responsible for the decreased immune response in the EAE rats is strongly supported by the similar decreased severity in the clinical symptoms and brain and spinal cord histopathological lymphocyte infiltrations with conivaptan, a specific V1a-V2 AVP receptors antagonist ( Quintanar-Stephano et al, 2012 ; Quintanar-Stephano et al, 2019 , 2018 ; Viñuela-Berni et al, 2020 ; Figure 2 ). On the other hand, Bossinger suggested that the administration of OXT in patients with MS during aggravation or remission periods alleviates the symptoms ( Bossinger, 1966 ); however, AVP and OXT can bind to V1a and V2 receptors ( Terrillon et al, 2003 ).…”
Section: Introductionmentioning
confidence: 85%
“…Experiments on Wistar and Lewis rat strains, subjected to neurointermediate pituitary lobectomy (NIL) induced a permanent decrease in AVP and oxytocin (OXT) serum levels. Immune studies in these animals showed that innate, humoral, and cell mediated immune responses were decreased (not suppressed) ( Quintanar-Stephano et al, 2012 ; Quintanar-Stephano et al, 2019 ). Experiments in NIL Lewis rats immunized for EAE, showed that NIL animals developed just a mild clinical symptom of EAE, whereas desmopressin administration (an agonist of V2 AVP receptors) restored the susceptibility of these animals to EAE ( Quintanar-Stephano et al, 2016 , 2012 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation